ANALISIS NILAI-NILAI PENDIDIKAN ISLAM PADA FILM JERANGKUNG DALAM ALMARI SUTRADARA SHADAN HASHIM - Mansyah, Robi; Wardarita, Ratu (Scientia: Jurnal Hasil Penelitian, 2022)
This study entitled "Analysis of Islamic educational values ​​in the film Jerangkung in the closet of director Shadan Hashim". This study examines the values ​​of Islamic education in a film Jerangkung Dalam Almari directed by Shadan Hashim. This study aims to describe the values ​​of Islamic education in the film Jerangkung Dalam Almari. The data source of this research is the film Jerangkung Dalam Almari. The method used in this research is descriptive qualitative research method. Collecting data in this study using documentation. The data analysis technique used is a content analysis technique. The study of the values ​​of Islamic education is therefore grouped into three groups: the main categories, namely (1) the value of education in faith (aqidah) including education that seeks to introduce, instill and direct students to the values ​​of belief in the pillars of Islam and the like, ( 2) the value of education for worship (shari'ah) including education that seeks to recognize, appreciate and instill the values ​​of God's rules regarding the procedures for behaving in human life, both vertical and horizontal relationships with His creatures, and (3) the value of moral education includes values ​​education that seeks to introduce, instill and remind students of the value rule system that regulates patterns of behavior, attitudes and behavior of human actions on the contents of the earth, which includes relationships with God, relationships with other humans, and relationships with oneself.